Co-occurrence perspective of arsenic and fluoride in the groundwater of Diphu, Assam, Northeastern India. (May 2016) - Kumar, Manish; Das, Aparna; Das, Nilotpal; Goswami, Ritusmita; Singh, Umesh Kumar
Abstract: Considerable lacunae exists in As and F − co-contamination investigation in the Brahmaputra and Gangetic floodplains. Therefore we selected Diphu a township in the Karbi Plateau rising from the Brahmaputra floodplains for evaluation of As and F co-occurrence, correlation with coexisting ions of the aquifer system and elucidation of potential processes for releasing As and F − in the groundwater. Our initial appraisal used generic plots for identification of hydro geochemical processes and major water types. Subsequently, As and F − co-occurrence with pH, depth, HCO3 −, SO4 2−, Ca 2+ and Fe were probed for possible correlation followed by hierarchical cluster analyses to identify key processes for co-occurrence. Finally, saturation indices of groundwater minerals were calculated using MINTEQA2 to elucidate prospective As and F − release into groundwater. Results indicate F − and As presence in Ca–HCO3 rich water along with positive correlation between Ca 2+ and F − possibly due to limestone reserves in adjoining areas. Multivariate analyses suggest the presence of high concentrations of PO4 3−, and H4 SiO4 either individually or in combination can enhance the mobility of both As and F − and possibly abet conditions conducive for co-contamination of aquifers. Initial release of As and F − from the parent rock seems driven by the anthropogenic activities while mobilization depends on chemical interactions and individual affinities of the elements. The results of speciation highlight further mobilization of As and F − into the groundwater which in turn require regular attention for sustainable management of scarce water resource present in the area. Highlights: Application of speciation and cluster analyses to understand co-contamination. Two contaminants were not found strongly correlated in their distribution. PO4 3−, HCO3 −, and H4 SiO4 enhance the mobility of both As and F − . Initial release of As and F − seems driven by anthropogenic activities. Mobilization depends on individual chemical affinities of the elements (As or F − ).